Is the use of metformin in patients undergoing dialysis hazardous for life? A systematic review of the safety of metformin in patients undergoing dialysis. Issue 12 (9th December 2019) - Abdel Shaheed, Christina; Carland, Jane E.; Graham, Garry G.; Stocker, Sophie L.; Smith, Greg; Hicks, Mark; Williams, Kenneth M.; Furlong, Timothy; Macdonald, Peter; Greenfield, Jerry R.; Smith, Felicity C.; Chowdhury, Gina; et al.
Abstract : Aims: Metformin may have clinical benefits in dialysis patients; however, its safety in this population is unknown. This systematic review evaluated the safety of metformin in dialysis patients. Methods: MEDLINE, Embase, CENTRAL, PsycINFO and the Cochrane Library were searched for randomised controlled trials and observational studies evaluating metformin use in dialysis patients. Three authors reviewed the studies and extracted data. The primary outcomes were mortality, occurrence of lactic acidosis and myocardial infarction (MI) in patients taking metformin during dialysis treatment for ≥12 months ( long term ). Risk of bias was assessed using Risk Of Bias In Nonrandomised Studies of Interventions (ROBINS‐1). Overall quality of evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Fifteen observational studies were eligible; 7 were prospective observational studies and 8 were case reports/case series. No randomised controlled trials were identified. The 7 prospective observational studies ( n = 194) reported on cautious metformin use in patients undergoing maintenance dialysis. Only 3 provided long‐term follow‐up data. In 2 long‐term studies of metformin therapy (≤1000 mg/d) in patients undergoing peritoneal dialysis (PD), 1 reported 6 deaths (6/83; 7%) due to major cardiovascular events (3 MI) and the other reported no deaths (0/35). One long‐term study of metformin therapy (250 mg to 500 mg thrice weekly) in patients undergoing haemodialysis reported 4 deaths (4/61; 7%) due to major cardiovascular events (2 MI). These findings provide very low‐quality evidence as they come from small observational studies. Conclusion: The evidence regarding the safety of metformin in people undergoing dialysis is inconclusive. Appropriately designed randomised controlled trials are needed to resolve this uncertainty.